Measuring Reasoning in Paranoia: Development of the Fast and Slow Thinking Questionnaire. Issue 1 (10th July 2020) - Hardy, Amy; Tolmeijer, Eva; Edwards, Victoria; Ward, Thomas; Freeman, Daniel; Emsley, Richard; Green, Catherine; Rus-Calafell, Maria; Greenwood, Kathryn; Bebbington, Paul; Kuipers, Elizabeth; Fowler, David; et al.
Abstract: Paranoid thoughts are common across the psychosis continuum. It is well established that reasoning biases (conceived as an overreliance on fast thinking and lack of willingness and/or ability to engage in slow thinking) contribute to paranoia. Targeted therapies have shown promise in improving reasoning in order to reduce paranoia. Psychometrically robust and easy-to-use measures of these thinking styles will assist research and clinical practice. Existing assessments include experimental tasks that are complex to administer or self-report measures that have limitations in comprehensively assessing cognitive biases in paranoia. We have developed the first questionnaire to assess fast and slow thinking biases related to paranoid thoughts, and here report on its evaluation. In study 1, we generated, evaluated, and extracted items reflecting reasoning, and assessed their reliability and validity in a non-clinical sample ( n = 209). In study 2, we replicated the factor analysis and psychometric evaluation in a clinical sample ( n = 265). The resultant Fast and Slow Thinking (FaST) questionnaire consists of two 5-item scales reflecting fast and slow thinking and is therefore brief and suitable for use in both research and clinical practice. The fast thinking scale is reliable and valid. Reliability and criterion validity of the slow scale shows promise. It had limited construct validity with objective reasoning assessments in the clinical group, possibly due to impaired meta-cognitive awareness of slow thinking. We recommend the FaST questionnaire as a new tool for improving understanding of reasoning biases in paranoia and supporting targeted psychological therapies.